Publishing with Open Research Europe: using open science principles for scholarly communication, collaboration and dissemination - Fisher, R; Doffegnies, A (Bodleian Libraries, University of Oxford, 2023)
Open Research Europe (ORE) is the European Commission’s recently launched open science platform, designed for Horizon 2020 and Horizon Europe-funded researchers across all academic disciplines to publish their research. Eligible researchers include those who are part of the European Research Council projects and Marie Skłodowska-Curie Actions, as well as ERA-Net and Euratom projects and members of COST Actions. The platform functions with a Diamond open access model, meaning that there are no author-facing fees for publishing open access articles. This seminar will explore: The benefits of publishing using ORE’s innovative and transparent model of open, post-publication peer review